Does the utilisation of dolphin kicks during backstroke finishes impact swimming performance in pubertal swimmers? - Papadimitriou, K.; Papadimitriou, N. (International Journal of Performance Analysis in Sport, 2024)
Aim of the study was the comparison of three backstroke finishes and their probable correlation with dolphin kicks ability on swimming efficiency and performance. Thirty swimmers (9 males - 21 females), aged 13.4 (1.0) years old, with a training experience of 7.7 (1.5) years, swam for 15 m on maximal intensity, and performed the three backstroke finishes: i) touching the wall, breaking water`s surface with one part of their body (Classic), ii) touching the wall with one hand, submerging the body two strokes after passing the last 5 m (Dive - One Hand) and iii) touching the wall on streamline position, submerging the body two strokes after passing the last 5 m (Dive - Streamline). It employed a two-way analysis of variance with repeated measures and a correlation analysis. According to the results, there was a difference between, Classic, Dive - One hand, and Dive - Streamline in swimming speed (SS) at the last 5 m (p = 0.001). Also, the SS between intermediate 10 and the last 5 m was maintained only in Classic type (p < 0.001). In addition, the three types of backstroke finishes were highly correlated (p < 0.001) with the dolphin kicks ability. Swimming coaches have to consider the swimmers` dolphin kicks ability for the choice of the ideal type of backstroke finish.